PENGAWASAN DINAS PEMBERDAYAAN MASYARAKAT DAN DESA (DPMD) KABUPATEN BENGKALIS TERHADAP USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) PERDANA MANDIRI SEJAHTERA TAHUN 2017 - Muhammad Izzan Subpriadi; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The weak selection process for the feasibility of beneficiaries of funds and during assistance in using the Village Economic Business Fund-Savings and Loans (UEK-SP) Perdana Mandiri Sejahtera has an impact on the amount of refunds that have been distributed not in accordance with expectations, this is due to weak supervision carried out so that the employees do their own way without paying attention to what has become a reference. The formulation of the research problem is how is the supervision of the Bengkalis Community and Village Empowerment Service (DPMD) on the Economic Business of the Perdana Mandiri Sejahtera Village of Savings and Loans (UEK-SP) in 2017 ?, and what factors are obstacles to the supervision of the Community and Village Empowerment Service (DPMD) ) Bengkalis Regency to Perdana Mandiri Sejahtera Economic Business Village (UEK-SP) in 2017 ?. The research objective was to determine the supervision of the Bengkalis Regency Community and Village Empowerment Service (DPMD) on the Economic Business of the Perdana Mandiri Sejahtera Village of Savings and Loans (UEK-SP) in 2017, and to determine the factors that become obstacles in the supervision of the Community and Village Empowerment Service ( DPMD) Bengkalis Regency on the Economic Business of the Perdana Mandiri Sejahtera Savings and Loan Village (UEK-SP) in 2017 Supervision of the Bengkalis Community and Village Empowerment Service (DPMD) is only guided by the rules made by UEK-SP, determining the measurement of the implementation of activities in 2 ways, namely visiting directly to the business location and by telephone followed by sending data via e-mail, measurement implementation is to directly conduct checks in the field, in comparing the implementation, it is found that there are implementation standards that are not in accordance with the implemented practice, the inhibiting factor in supervision is the not yet established implementation standards and limited human resources. Keywords: Supervision, Savings and Loan (UEK-SP) Urban Village Economic Enterprises